EFFECT OF BIO FERTILIZER ON HEAVY METALS IN RHIZOSPHER OF POTATO - Abdulsada, Ali jabbar; Dheyab, Naeem Saeed; Mutlag, Khamees Habeeb; Hasoon, Wafaa Hadi; Aboud, Hadi Mahdi (Diyala Agricultural Sciences Journal, 2020)
To evaluated the role of bio agent Mycorrhiza fungi (Glomus sp) and bacteria (Azotobacter chrococcum) in the rhizospher which accumulated by heavy metals. the results were showed that in comparison to the soil which not inoculated ، the heavy metals (Ni، Fe، Mn، Zn، Cu and Co) decrease from ( 0.325، 86.5 60، 1.493، 0.576، 0.034 and 0.019 mg/g soil ) respectably from control treatment to ( 0.261، 76.460، 1.329، 0.416، 0.015 and 0.017 mg/g soil) respectively from interaction treatment between fungi and bacteria in spring season, the same results were obtain in the autumn season ، heavy metal decreased from (0.347، 90.16، 1.693، 0.612، 0.054 and 0.048 mg/g soil) respectively from control treatment to (0.2880، 80.06، 1.629، 0.459، 0.036 and 0.047 mg/g soil ) respectively from interaction treatment between fungi and bacteria.